La politique de conservation-restauration du patrimoine en France - Roland May (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The conservation-restoration policy of the public legacy that stands in France is strongly supervised by state officers but, paradoxically, Culture Heritage Institutions have no restorator. In the last thirty years, appeared some light changes despite decentralization; but at the end of the nineties, changes improved a lot, with the establishment of public contracts, along with the State being less present, underlining in this way the liberal status of conservation-restoration. In our days, these changes have, more or less, reached their term and it would be relevant to redefine a public policy concerning conservation-restoration.